Prevalence of Haplorchis taichui and Haplorchoides sp. metacercariae in freshwater fish from water reservoirs, Chiang Mai, Thailand - Nithikathkul C. (2014)
A parasitological investigation on trematode metacercariae was made on 62 freshwater fishes of 13 species in northern Thailand; Cyclocheilichthys apogon, Puntioplites proctozysron, Labiobarbus siamensis, Barbodes gonionotus, Barbodes altus, Henicorhynchus siamensis, Osteochilus hasselti, Notopterus notopterus, Mystacoleucus marginatus, Anabas testudineus, Systomus orphoides, Morulius chrysophykadian, and Hampala macrolepidota. The fish were caught over the summer period (February-May 2007) from 2 Chiang Mai water reservoirs, i.e., the Mae Ngad (UTM 47Q E 503200, 47Q N 2119300) and the Mae Kuang Udomtara (UTM 47Q E 513000, 47Q N 2092600) Reservoirs in Chiang Mai province, Thailand. The prevalence of heterophyid (Haplorchis taichui and Haplorchoides sp.) metacercariae in these fish was 83.9% and 74.2% in the Mae Ngad and Mae Kuang Udomtara Reservoirs, respectively. The highest intensity of heterophyid metacercariae in H. siamensis in the Mae Ngad was 120.4 and that in P. proctozysron in the Mae Kuang Udomtara was 180.0. The fish, A. testudineus, C. apogon, and M. chrysophykadian, were not found to be infected with H. taichui metacercariae. The results show that the freshwater fish in Chiang Mai water reservoirs are heavily infected with H. taichui and Haplorchoides sp. metacercariae.